Head wounds - McGarrity, Michael (McGarrity, Michael. Kevin Kerney novel., 2021)
"Detective Clayton Istee investigates New Mexico borderland killings by an elusive Mexican assassin with ties to a drug cartel. In Michael McGarrity's final, propulsive Kevin Kerney novel, the nightmare of the Mexican drug wars spills across the border with the discovery of a couple in a Las Cruces hotel, scalped with their throats cut. Because of the unusual MO, Detective Clayton Istee suspects that the murders are drug related, but a lack of evidence stalls his investigation. Turning to the victims for a possible motive, he learns that two years ago the couple had stolen $200,000 from a nearby casino, then disappeared. When his efforts to uncover why they'd unexpectedly returned fail to generate any leads, he resists letting the case go cold. Approached by a seasoned DEA agent working undercover to seize the assassin, Clayton is thrust into the Mexican underworld of police corruption, narcotrafficking, money laundering, and dirty federal officials on both sides of the Rio Grande. What unravels culminates in a ferocious climax that is sure to stun"--